Old age pensions and retirement in Spain - Raquel Vegas Sánchez; Isabel Argimón; Marta Botella; Clara I. González (SERIEs - Journal of the Spanish Economic Association, 2013)
In this paper we analyze the influence that incentives play in the timing of the transition to retirement in Spain. We use the Continuous Sample of Working Histories 2006 (CSWH 'Muestra Continua de Vidas Laborales', in Spanish) to construct incentive measures from the Social Security provisions in relation to retiring at old age. We analyse the role played by such incentives and other socio-economic variables on the retirement hazard of men aged between 60 and 70, using a duration model to carry out a dynamic analysis. We assess the effects of the pension system reform that took place in 2002, which set stricter conditions to access an old pension. The results show that both the pension wealth and the substitution effects play a significant role in retirement decisions, but that, after the reform, the latter effects become less important.
Keywords: J14; J26; 330; older workers employment; retirement; public pensions; Flexible Altersgrenze; Anreiz; Gesetzliche Rentenversicherung; Spanien